Disaster Olympics: A Model for Resident Education. Issue 3 (6th April 2016) - Daniel, P.; Gist, R.; Grock, A.; Kohlhoff, S.; Roblin, P.; Arquilla, B.
Abstract: Objectives: The aim of this study was to describe an educational method teaching Disaster Medicine to American Emergency Medicine (EM) physicians and to evaluate knowledge attainment using this method. Methods: This was an observational study using a pre-test and a post-test. A full-scale disaster exercise (FSE) was conducted at a large academic center with two hospitals in Brooklyn, New York (USA). Eighty-two EM residents (physicians in training, post medical school) participated in the study. Inclusion criteria for study participation was all EM residents training at the State University of New York (SUNY) Downstate at the time of the study. There were no exclusion criteria. The exercise was a disaster drill designed as "Olympic Games." Participants in the exercise took a pre-test and a post-test. The primary outcome of the study was the mean difference between pre-test and post-test scores of the study participants using independent sample t-tests. Secondary outcomes of the study were percent of critical actions met by the residents and the hospitals as measured by direct observation of trained study personnel during the exercise. Results: Mean resident post-test scores were higher than pre-test scores to a degree that was statistically significant (62% versus 53%; P =.002). The residents' performances ranged from 48% to 63% of objectives met. The hospitals' performances met 50% to 100% of their objectives. Conclusion: The use of an Olympic Games format was an effective model for disaster education for physicians. The model allowed for evaluation of performance and protocols of participants and hospital systems, respectively, and may be used objectively to evaluate for areas of improvement. The Disaster Olympics drill was found to improve emergency preparedness knowledge in the population studied and may constitute a novel and efficacious methodology in disaster training. P Daniel, R Gist, A Grock, S Kohlhoff, P Roblin, B Arquilla .Disaster Olympics: a model for resident education .Prehosp Disaster Med .2016 ;31 (3 ):237 –241 .